Ode to a banker - Davis, Lindsey (New York : Mysterious Press, 2001)
Can a tough detective possess the soul of a poet? After a public reading brings him rousing applause, Falco receives an offer to have his work published. But his ego takes a beating when the banker Chrysippus demands payment for putting the verse on papyrus. Hell hath no fury like an author scorned, and when Chrysippus turns up murdered - in the library, no less - it's poetic justice. Appointed the official investigator, Falco's soon up to his stylus in outraged writers and shifty bankers. Now it's time to employ his real talents: deducing the killer from an assembly of suspects.
85408
Keywords: Falco, Marcus Didius (Fictitious character) -- Fiction; Private investigators -- Rome -- Fiction; Rome -- History -- Vespasian, 69-79 -- Fiction; Historical fiction; Mystery fiction